Menstrual dysfunction and bone health in female athletes - Bass, S.; Kerr, D. (International SportMed Journal, 2001)
Female athletes are generally considered to be at low risk of osteoporosis because of the skeletal loading associated with sports participation. Sites that are exposed to long-term high-impact loading are consistently reported to be higher than the same sites in their sedentary peers. However, weight-bearing exercise does not always ensure that athletes will have high bone-mineral density, as the hormonal environment, dietary factors, and loading history all influence bone-mineral density. In particular, menstrual dysfunction, which can occur with intense training or disordered eating, is a significant risk factor for low bone-mineral density. Exercise history before menstrual dysfunction is likely to offer some protection for low bone-mineral density, particularly at the hip. Resumption of menses is unlikely to restore bone-mineral density to levels reported in eumenorrheic athletes or even sedentary peers. Athletes at risk of amenorrhea should be identified and their training loads and energy intakes monitored to ensure normal menstrual function. Athletes who remain amenorrheic should be counseled about the possible negative effects of amenorrhea and monitored for bone loss. Early intervention is recommended for amenorrheic athletes with low bone-mineral density.